2020
DOI: 10.2147/ijwh.s249619
|View full text |Cite
|
Sign up to set email alerts
|

<p>The Impact of Spinal Anesthesia and Use of Oxytocin on Fluid Absorption in Patients Undergoing Operative Hysteroscopy: Results from a Prospective Controlled Study</p>

Abstract: The aim of this study was to determine if combining intravenous oxytocin infusion and spinal anesthesia will reduce the amount of glycine absorption in patients undergoing operative hysteroscopy. Patients and Methods: A prospective controlled study was conducted in premenopausal patients who had hysteroscopic surgery including endometrial resection, endometrial polypectomy, myomectomy resection and uterine septal resection. The effect of combined spinal anesthetic with oxytocin infusion on fluid deficit was st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 31 publications
0
5
0
Order By: Relevance
“…It was suggested that there was almost no difference in the effect of general anaesthesia and spinal anaesthesia on the blood pressure of patients during hysteroscopic surgery, regardless of the different absorption of glycine or the same absorption of normal saline. The main reason for this result is that the difference in the absorption of glycine between the two groups was only approximately 560 ml in previous studies [ 13 ]. Most of the hypotonic glycine solution absorbed into the vascular system was quickly transferred into the tissue and cells in the body, and the amount of glycine left in the circulatory system was relatively small, which had little effect on the circulation.…”
Section: Discussionmentioning
confidence: 81%
“…It was suggested that there was almost no difference in the effect of general anaesthesia and spinal anaesthesia on the blood pressure of patients during hysteroscopic surgery, regardless of the different absorption of glycine or the same absorption of normal saline. The main reason for this result is that the difference in the absorption of glycine between the two groups was only approximately 560 ml in previous studies [ 13 ]. Most of the hypotonic glycine solution absorbed into the vascular system was quickly transferred into the tissue and cells in the body, and the amount of glycine left in the circulatory system was relatively small, which had little effect on the circulation.…”
Section: Discussionmentioning
confidence: 81%
“…ere was a statistically significant less mean fluid deficit in the study group than the control group in endometrial polypectomy and myomectomy patients but not in those who underwent septal resection [21]. e 1.5% glycine is one of the most common solutions used in monopolar hysteroscopic procedures due to its nonhemolytic, nonconductive, and transparent properties, although it is more toxic and has poorer outcomes when confronted with other options [22].…”
Section: Discussionmentioning
confidence: 86%
“…They presumed that using low-dose oxytocin (10 international units (IUs) in 200 mL normal saline) would stimulate uterine contractions compressing the myometrial vessels and reduce the glycine absorption. There was a statistically significant less mean fluid deficit in the study group than the control group in endometrial polypectomy and myomectomy patients but not in those who underwent septal resection [ 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…30 Al Husban et al compared neuraxial anesthesia with concomitant oxytocin infusion with general anesthesia alone and found significantly lower fluid deficit in the former group (mean deficit 439.25 mL vs 631.75 mL, P <.05); however, the presence of two variables in the intervention group confounds any further analysis. 35 Lastly, a study by Munmany et al published in 2016 compared propofol infusion with inhaled sevoflurane at the time of operative hysteroscopy and noted a significantly lower deficit for the group receiving propofol (median deficit 202 mL, range 60–542 mL vs median deficit 264, range 153–932, P =.007). 33…”
Section: Resultsmentioning
confidence: 98%